The use of traditional project - Clayton, Beverley Alice (My University, 2011)
Project management was, in its formative stages, found only in specific industries like defence and technology. It has more recently become common across many sectors and has been, formally or informally, adopted as an effective business tool. The purpose of this research was to explore the presence and usage of project management in creative industries and to determine the effectiveness of the methods used by creative people. The answers to the following two research questions were established through the research conducted. The questions asked “do project managers in creative industries use traditional project management techniques to get their jobs done or do they rely on what they have learned through experience?” and “what are the barriers to effective project management as perceived by project managers in creative industries?”. Data was collected from 15 individuals who manage work in television production and event management. These respondents took part in in-depth interviews where they provided information on their method of managing projects and gave information about themselves and their careers. They also completed a short questionnaire on project management. The interview data was analysed using a themed content analysis approach and the research results were presented using the thick descriptive technique. The results of the study indicated that persons working in creative industries are neither aware of, nor make use of traditional project management techniques except in some cases where those techniques happen to be coincidentally similar to something they have already learned. Traditional project management techniques do exist in creative industries but occur more out of coincidence than conscious thought. The results also indicated that persons working in creative industries believe that the constraints of cost and speed present problems in achieving effective iii outcomes and work with creative people does not lend itself to using formal project management techniques
MBA - WBS
Keywords: Project management; Creative industries, South Africa